Immune cell residency in the nasal mucosa may partially explain respiratory disease severity across the age range - Winkley, Konner; Banerjee, Dithi; Bradley, Todd; Koseva, Boryana; Cheung, Warren A.; Selvarangan, Rangaraj; Pastinen, Tomi; Grundberg, Elin (Scientific reports, 2021)
Previous studies focusing on the age disparity in COVID-19 severity have suggested that younger individuals mount a more robust innate immune response in the nasal mucosa after infection with SARS-CoV-2. However, it is unclear if this reflects increased immune activation or increased immune residence in the nasal mucosa. We hypothesized that immune residency in the nasal mucosa of healthy individuals may differ across the age range. We applied single-cell RNA-sequencing and measured the cellular composition and transcriptional profile of the nasal mucosa in 35 SARS-CoV-2 negative children and adults, ranging in age from 4 months to 65 years. We analyzed in total of ~ 30,000 immune and epithelial cells and found that age and immune cell proportion in the nasal mucosa are inversely correlated, with little evidence for structural changes in the transcriptional state of a given cell type across the age range. Orthogonal validation by epigenome sequencing indicate that it is especially cells of the innate immune system that underlie the age-association. Additionally, we characterize the predominate immune cell type in the nasal mucosa: a resident T cell like population with potent antiviral properties. These results demonstrate fundamental changes in the immune cell makeup of the uninfected nasal mucosa over the lifespan. The resource we generate here is an asset for future studies focusing on respiratory infection and immunization strategies.